On the asymptotic partition of energy in the theory of swelling porous elastic soils (Archives of Mechanics - Test, 2003)
The Cesàro means of various parts of the total energy are introduced in the context of the linear theory of swelling porous elastic media. Then, the relations describing the asymptotic behaviour of the Cesàro means are established.